Functional managerial competencies of women managers and entrepreneurs - Custodio, Lily P. (Philippine Journal on Innovation and Entreperneurship, 2013)
This study determined the importance of using functional management areas in discharging the duties and functions of organization executives. The managerial competencies of women managers and entrepreneurs in Catanduanes were investigated. The descriptive method of research was used with the questionnaire as the main tool in gathering the data. Respondents of the study included women managers and entrepreneurs in the provinve and three of their subordinates. Convenience sampling and quota sampling were used. Statistical tools used included frequency count, percentage, weighted mean, and t-test. The study ascertained that: (1) the managerial competencies of women managers and entrepreneurs as perceived by them and their subordinates are highly important in discharging managerial duties and functions; (2) the managerial competencies on (a) strategic thinking and scenario building , (b) analysis, problem solving, and decision making, (c) planning and organizing, and (d) change management were perceived differently by the executives and their subordinates; and (3) the executives had similar perceptions of their competencies on the 13 functional management areas investigated in the study. Recommendations are offered, and mnagerial implications of the study are emphasized.